2016
DOI: 10.1155/2016/9648473
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nonunion Avulsion Fracture of the Anterior Tibial Eminence

Abstract: Avulsion fracture of the anterior tibial eminence is an uncommon injury. If bone union does not occur, knee extension will be limited by impingement of the avulsed fragment and knee instability will be induced by dysfunction of the anterior cruciate ligament (ACL). This report describes a 55-year-old woman who experienced an avulsion fracture of the right anterior tibial eminence during recreational skiing. Sixteen months later, she presented at our hospital with limitation of right knee extension. Plain radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Atusmi et al reported that arthroscopic debridement of the anterior scar of a bone fragment improved extension limitation in a case of tibial ACL avulsion fracture nonunions with extension limitation as the primary complaint [ 6 ]. This has the advantage of being minimally invasive and is a good indication for middle-aged and older patients who are not highly active in sports [ 6 ]. Keys and Walters reported a case of nonunited tibial ACL avulsion fractures with a one-year-long pain on extension, which was successfully treated with fresh bone fragments, bone grafting, and screw fixation by open surgery [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atusmi et al reported that arthroscopic debridement of the anterior scar of a bone fragment improved extension limitation in a case of tibial ACL avulsion fracture nonunions with extension limitation as the primary complaint [ 6 ]. This has the advantage of being minimally invasive and is a good indication for middle-aged and older patients who are not highly active in sports [ 6 ]. Keys and Walters reported a case of nonunited tibial ACL avulsion fractures with a one-year-long pain on extension, which was successfully treated with fresh bone fragments, bone grafting, and screw fixation by open surgery [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tibial ACL avulsion fractures require appropriate treatment because of complications such as limited extension, instability, and residual pain, as well as nonunion and deformity, if not treated appropriately [3]. Previously reported treatment options for tibial ACL avulsion fractures include osteosynthesis by open reduction, osteosynthesis with arthroscopy, debridement with arthroscopy, and ACL reconstruction [4][5][6][7]. On the other hand, the treatment of tibial ACL avulsion fracture nonunions is even rarer and less frequently reported, and the optimal treatment modality has not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…Torisu 4 reported treatment of 2 cases of delayed union and 1 case of nonunion with staple fixation. Although various forms of treatment and fixation have successfully been used to treat symptomatic nonunion of anterior eminence avulsion fractures [14][15][16][17] , these 2 case series demonstrate the only reported methods of fixation for symptomatic delayed or nonunion of PCL avulsions. This case report adds a third method for successful fixation of a symptomatic nonunion of the posterior tibial eminence.…”
Section: Discussionmentioning
confidence: 99%
“…Ossicles are a frequent finding and usually require no further therapy. On the other hand, through their relation to tendons or ligaments, avulsion fractures are frequently considered as "complex fractures" and require conservative and -in some cases -surgical management [2][3][4]. Thus, the clear differentiation between ossicles and avulsion fractures, even in anatomically difficult regions, is an important aspect of the radiologist's report [5].…”
Section: Introductionmentioning
confidence: 99%